1999
DOI: 10.1142/s0218202599000129
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Finite Element Methods for Reactive Compressible Flow

Abstract: We extend the adaptive streamline diffusion finite element method for compressible flow in conservation variables using P1× P0 space–time elements to include chemical reactions. The adaptive error control is based on an a posteriori error estimate involving a stability factor, which is estimated numerically. We prove for a model problem that the stability factor is bounded by a moderate constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…To proceed we use the following interpolation estimates, proofs of which can be found in [13] and [15]:…”
Section: Notationsmentioning
confidence: 99%
“…To proceed we use the following interpolation estimates, proofs of which can be found in [13] and [15]:…”
Section: Notationsmentioning
confidence: 99%
“…Of course, to do this numerically we would have to choose a finite number of right-hand side functions ψ, and take the supremum for C s,j over this set of trial functions. This approach has been implemented by Sandboge [20] for reactive flow problems. However, numerical computations based on this approach have shown that the individual stability constants may vary by as much as one or even two orders of magnitude depending on the function chosen to represent e.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The information carried by the dual solution is explicitly used in the form of local weights in our a posteriori error bounds. This combined analysis allows us to avoid stability constants as they appear in the general approach by Eriksson et al [10] (see also [30]), since accurate estimates of those are hardly available for nonlinear problems. Moreover, this concept seems to be particularly useful in case of strongly nonhomogeneous behavior of the original problem as in the present case.…”
Section: Equation (11) Is Supplemented By Initial and Boundary Condimentioning
confidence: 99%